WOMEN AND SPORTS - GENDER POLITICS IN CONTEMPORARY KERALA - Ashitha. M
This essay aims to analyze the relationship between patriarchy and sports in contemporary Kerala, southern state of India. By looking at the institutional and other realms of sports in the state, the paper explains how the gendered practice of sports marginalizes women in multiple ways. The experiences of female athletes and other sporting women illustrates the discrimination and exclusion prevails in this filed. The theoretical discussion on female body and sports unravels the complexities of the notion of masculinity and femininity. The empirical facts generated from the documents, writings on women experiences and the narratives of female athletes, substantiated the theoretical framework postulated on gender and sports in this essay. The social context of the Kerala society that acts as the ground for gendered practices in sports is brought into the picture. The review of the historical junctures of the complex relationship between sports and gendered practices in the world wide and India is juxtaposed with the Kerala scenario. It outlined the problems of Kerala sporting women and continuing legacy of gendered practices in Kerala.